The Prevalence and Causes of Visual Impairment in Type 2 Diabetes Mellitus in Northeast China - Liang Wen; Yu Wang; Zhong Lin; Feng Hua Wang; Xiao Xia Ding; Dong Li; Kemi Feng; Yuan Bo Liang; Dong Xiao Zhang; Yu Dou; Gang Zhai (Journal of Ophthalmology)
Purpose. To evaluate the prevalence and causes of visual impairment in a group of community people with type 2 diabetes mellitus (T2DM) in Northeast China. Methods. Population-based cross-sectional survey. Patients diagnosed with T2DM residing in 15 communities in Fushun, Northeast China, were enrolled between July 2012 and May 2013. All participants underwent an extensive and standardized eye examination (visual acuity testing, slit-lamp, and fundus examination). Low vision was defined as presenting VA of better-seeing eye <20/60 and ≥20/400, and blindness was defined as VA <20/400, according to the World Health Organization (WHO) definitions. The primary causes of blindness and low vision were assessed by senior ophthalmologists. Results. Visual acuity measurements were available for 1998 (89.8%) of 2224 subjects in the study. The prevalence of bilateral blindness and low vision defined was 0.90% and 10.81%. Uncorrected refractive error was the first leading cause of low vision (75.0%) and blindness (38.9%). After correcting the refractive error, the first leading cause of low vision was cataract (44.4%), followed by diabetic retinopathy (29.6%) and myopic maculopathy (18.5%), while the first leading cause of blindness was proliferative DR (45.4%), followed by cataract (36.4%) and myopic maculopathy (18.2%). Conclusions. This study suggested a high prevalence of low vision and blindness in this study cohort. Uncorrected refractive error and cataract remain the leading cause of visual impairment, but the major challenge is the early diagnosis and intervention of diabetic retinopathy to reduce diabetes-related blindness.